Work Function and Electron Affinity of Semiconductors: Doping Effect and Complication due to Fermi Level Pinning - Shao, Guosheng (Energy & environmental materials (Hoboken, N.J.), 2021)
Semiconductors are a major category of functional materials essential to various applications to sustain the modern society. Most applied materials or devices utilizing semiconductors are enabled by interfaces or junctions, such as solar cells, electronic/photonic devices, environmental sensors, and redox hetero‐catalysts. Herein, the author provides a critical commentary on photoemission measurement of the work function and, more importantly, the electron affinity of semiconductors essential for energy band diagram of heterojunctions. Particular effort is made towards addressing complications associated with Fermi level pinning due to surficial states of doped semiconductors. UPS measurement of work functions and band edge levels of semiconductors, with particular focus on addressing complication due to Fermi level pinning.